Thermal analysis and CW laser operation at 1.998 µm in end pumped Tm:YAP lasers - El-Agmy, Reda M.; Al-Hosiny, Najm M. (Photonics Letters of Poland, 2019)
We report on thermal analysis and a continuous wave (CW) laser operation at (1.998µm) of end pumped Tm: YAP cylindrical laser rod. The Tm: YAP laser rod is pumped at a wavelength of 1.064 µm emitting from Nd: YAG laser source. A 3W incident pump power is used to generate a maximum laser output of 700 mW, representing 18% slope efficiency. The power of thermally induced lens in Tm:YAP laser rod is numerically analyzed and validated experimentally. The focal lengths of the thermally induced lens are directly measured using Shack-Hartmann wavefront sensor. We have detected blue up-conversion fluorescence emission before laser operation at 1.998 µm. The obtained experimental results were in good agreement with the numerical calculations. Full Text: PDF References I. F. Elder, J. Payne, "Diode-pumped, room-temperature Tm:YAP laser", Applied Optics 36 (33), 8606 (1997) CrossRef Y. Li, B. Yao, Y. Wang, Y. Ju, G. Zhao, Y. Zong, J. Xu, "High efficient diode-pumped Tm:YAP laser at room temperature", Chinese Opt. Lett. 5 (5), 286 (2007). DirectLink H. Ni, S. C. Rand, "Avalanche upconversion in Tm:YALO3", Opt. Lett. 16 (8), 1424 (1991). CrossRef Z. G. Wang, C. W. Song, Y. F. Li, Y. L. Ju, Y. Z. Wang, "CW and pulsed operation of a diode-end-pumped Tm:GdVO4 laser at room temperature", Laser Phys. Lett. 6 (2), 105 (2009). CrossRef Baoquan Yao, Yi Tian, Wei Wang, Gang Li, Yuezhu Wang, "Analysis and compensation of thermal lens effects in Tm:YAP lasers", Chinese Opt. Lett. 8 (10), 996 (2010). CrossRef F. Cornacchia, D. Parisi, C. Bernardini, M. Toncelli, "Efficient, diode-pumped Tm3+:BaY2F8 vibronic laser", Opt. Expr. 12 (9), 1982 (2004). CrossRef Xiaojin Cheng, Mi Fan, Jiandong Cao, Jianhua Shang, "Research on the thermal effect and laser resonator of diode-pumped thin-slab Tm:YAP lasers", Optik 176, 32 (2019). CrossRef W. Koechner, Solid-state Laser Engineering, Springer, (2013). DirectLink https://www.crytur.cz DirectLink http://www.laserlabcomponents.com/ DirectLink R. M. El-Agmy, N.AlHosiny, "2.31 [micro sign]m laser under up-conversion pumping at 1.064 [micro sign]m in Tm3+:ZBLAN fibre lasers", Elect. Lett. 46 (13), 936 (2010). CrossRef R. M. El-Agmy, N. M. Al-Hosiny, "870 mW blue laser emission at 480 nm in a large core thulium doped ZBLAN fiber laser", Laser Phys. 20 (4), 838 (2010). CrossRef R. M. El-Agmy, N. M. Al-Hosiny, "Power scaling of end-pumped Nd:YLF lasers, modeling and experiments", Optik 140, 584 (2017). CrossRef R. M. El-Agmy, N. Al-Hosiny, "Thermal analysis and experimental study of end-pumped Nd: YLF laser at 1053 nm", Photonic sensors 7 (4), 329 (2017). CrossRef S. C. Tidwell, J. F. Seamans, M. S. Bowers, A. K. Cousins, "Scaling CW diode-end-pumped Nd:YAG lasers to high average powers", IEEE J. Quantum Electron. 28, 997 (1992). CrossRef P. J. Hardman, W. A. Clarkson, G. J. Friel, M. Pollnau, D. C. Hanna, "Energy-transfer upconversion and thermal lensing in high-power end-pumped Nd:YLF laser crystals", IEEE Journal of Quantum Electronics 35, 647 (1999). CrossRef